Smoke Indicator Alarms and Gas Sensors - Ab Aziz, Nurul Najihah; Sanusi @Ikhsan, Ts Mohd Hamim; Sanusi @Ikhsan, Ts Mohd Hamim; Salim, Natasya Nurshahira; Maseji, Khairunisa (Multidisciplinary Applied Research and Innovation, 2022)
This paper describes the design of a smoke indicator alarm and gas sensors with Arduino-based system by means of GSM module. However, depending on the features available on the safety system, smoke indicator alarms and gas sensors systems may not be inexpensive, and most safety systems can only provide local alarm, which means that property owners may not be aware of what is going on when an emergency occurs. The project's goal is to increase safety, with the main goal being to prevent fires from destroying inhabitants' homes and other property. The ATmega328p chip is used in conjunction with an Arduino Nano board. The ATmega328p is the main controller, and it controls the smoke indicator alarm and gas sensors that are exposed to the flame sensor and gas sensor. The smoke is detected using a MQ2 gas sensor, while the fire is detected using a flame sensor. A short messaging service SMS and a call to the registered number through GSM module will be sent to the user as an alarm message and call. When the gas sensor detects a smoke level of 200 or more, an alert signal is displayed on the LCD display immediately and it will send an SMS alert to the users, and if the flame sensor detects a fire, it will display the alarm on the LCD and phone the users. The test's findings are reported and analysed when there is a lot of smoke in the house. This technology can assist users in improving their safety standards by providing a quick response in the event of an accident. Users will be able to protect their lives and property from disasters as a result of this.